Självbekräftelse och nationalkaraktär i sportens värld - Schoug, Fredrik (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1993)
The present article intends to show how sports journalism functions as an active agent in the construction of national identities. Alongside the struggle on the field, this type of journalism engages in a duel of virtue, where the nature of the collective is often interpreted as nationally distinct. In juxtaposing Swedish team sports (primarily ice-hockey) with Russian, one sees that while the Swedish collective is described in positive terms such as "team moral", "team spirit", "camraderie" and "solidarity", the Russian collective is interpreted as being the result of oppression and submission. However, this ought not to be regarded as a simple reflection of old political habits. In sports research, sport is sometimes assigned a secondary role as merely the reflection of other historical, cultural and social factors. Such arguments ought to be dismissed, since they hide the productive role of sports in the construction of national (or other) identities. These subjective identities should not be primarily understood as correct descriptions of how "the Swedish" actually distinguishes itself from "the foreign", but rather as the expression of deeply-rooted national ideals. When sport harmonizes with other messages and experiences in this manner, cultural potentialities with enough force to saturate society in general can be formed.